Leveraging of dynamic export capabilities for competitive advantage and performance consequences: evidence from China - Efrat, Kalanit; Hughes, Paul; Nemkova, Ekaterina; Souchon, Anne L.; Sy-Changco, Joseph (Elsevier, 2018)
As the business arena becomes more global and therefore dynamic, organizations must balance their capabilities with the demands and the conditions of the international marketplace. This leads firms to trade off the development of more capabilities with the identification of core capabilities which can best improve export competitiveness and performance. Based on the Dynamic Capabilities Approach (DCA), we develop a model of four export capabilities, namely adaptability, innovativeness, unpredictability, and task-flexibility, aimed at achieving competitive advantage in foreign markets and enhance export performance. Based on a survey of 213 Chinese exporting organizations, we find out that innovativeness, unpredictability and task-flexibility are positively related to competitive advantage. Moreover, we uncovered that in the cases of adaptability, innovativeness and task-flexibility their impact on competitive advantage diminishes under higher levels of competitive intensity, however, for unpredictability this impact becomes negative. We also confirm the necessity of addressing competitive advantage separately from firms' performance.